O ser e o estar catador: experiências sociais no trabalho e nas tramas urbanas - Silva, Ari Rocha da (Universidade do Vale do Rio dos Sinos, 2018)
The purpose of this thesis is to understand the logic of the social actions of actors who participate in the execution of garbage recycling work in the city of Passo Fundo, RS, specifically collectors of recyclable materials, whether they are associated with cooperative enterprises or individual workers who collect on the streets of the city. The research proposal is based on the possibility of studying tangible experiences of workers in order to exemplify relational dynamics in a complex society. The individuals concerned are defined as social actors in order to build their relationships from their actions, between to be a collector and being a collector, in the spaces-times that integrate and negotiate their practices and interests. The theoretical contribution related to this reflection has an interface with the Sociology of Experiences by François Dubet and the analytical concepts of social and tactical provision, by Bernard Lahire and Michel de Certeau, respectively. Thus, it was condensed an analytical content embodied in a praxisology of social actors in their logics of integration, strategies / tactics and social subjectivation, since certain social events and processes can also be understood in the face of attitudes and dispositions that affect throughout life. This empirical survey was constituted through the application of 120 socioeconomic questionnaires along this public of urban workers, with a view to tracing an exploratory panorama of the study field and, on the face of it, the observation of certain characteristics that equal and distinguish the individuals concerned; in a second moment, it was carried out 22 narrative interviews with selected actors of this stratum in order to understand their social actions in face of their logics and life path. The study also allowed us to make direct observations in order to understand the conditions and realities experienced within this social segment. It should be considered, at last, that the collectors in Passo Fundo can be considered very heterogeneous individuals in their practices and attitudes, however, it is also necessary to consider them, overall, as subjects eminently changeable from the point of view of their displacements and how to develop adjustments in order to integrate themselves into the comprehensive society that welcomes them at certain moments and differentiates them and distances them in others.
Keywords: Trabalho; Atores Sociais; Vida cotidiana; Catadores; Passo Fundo; Work; Social actors; Everyday life; Collectors; Passo Fundo; ACCNPQ::Ciências Humanas::Sociologia